2016
DOI: 10.1016/j.biortech.2016.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moderate static electric field on the growth and metabolism of Chlorella vulgaris

Abstract: This post-print has been archived on the author's personal website (macc.mcmaster.ca) and/or the author's institutional repository (macsphere.mcmaster.ca) Abstract An electric field (EF) generator device was fabricated and applied to the treatment of Chlorella vulgaris ISC33 at three distinct concentrations before cultivation. The EF of moderate intensity (2.7 kVcm -1 ) has a hormetic effect on algal growth. The highest growth stimulation of 51% was observed after 50 min treatment of 0.4 g L -1 algal suspens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(15 citation statements)
references
References 37 publications
(55 reference statements)
1
13
0
Order By: Relevance
“…The response of Volvox algae to electric stimuli has been demonstrated, resulting to the polarization of their displacement in culture [112]. In C. vulgaris cultures, a 51% boost in the growth was achieved through the application of a 2.7 kV/cm static EF [113]. Using PEF of 40 kV/cm and 25 ns of duration, it was also possible to increase C. vulgaris biomass yield by 10-20% [114].…”
Section: Enhanced Mass Transferimproving Growth Kineticsmentioning
confidence: 99%
“…The response of Volvox algae to electric stimuli has been demonstrated, resulting to the polarization of their displacement in culture [112]. In C. vulgaris cultures, a 51% boost in the growth was achieved through the application of a 2.7 kV/cm static EF [113]. Using PEF of 40 kV/cm and 25 ns of duration, it was also possible to increase C. vulgaris biomass yield by 10-20% [114].…”
Section: Enhanced Mass Transferimproving Growth Kineticsmentioning
confidence: 99%
“…In a recent study, Nezammahalleh et al [70] showed that up to 73% of carotenoids (1.21 mg lutein Eq./g sample dw) can be recovered from the Heterochlorella luteoviridis microalga biomass using MEF combined with ethanol as solvent (180 V, 60 Hz, 75 mL/100 mL of ethanol solution). In this case, carotenoid extraction yield increased with electrical field strength and ethanol concentration.…”
Section: Nonconventional Extraction Of Carotenoidsmentioning
confidence: 99%
“…HPLC - UV - Vis analysis identified the presence of all -trans– lutein (856 μg/g), all -trans- zeaxanthin (244 μg/g) and all -trans- β - carotene (185 μg/g) in major quantities. Besides, all -trans -α-carotene, 9-13 - 15 -cis- β - carotene, cis- violaxanthin, all -trans- violaxanthin and 13-13′ -cis- lutein were detected in minor quantities [70]. In another study Jaeschke et al [64] used a two-stage approach to evaluate the effect of MEF pretreatment (0–180 V, 10 min) in the presence of 25 mL/100 mL of ethanol/water solution, followed by the subsequent extraction with ethanol at varying concentrations (25–75 mL/100 mL, 50 min) for the extraction of carotenoids from the microalga Heterochlorella luteoviridis .…”
Section: Nonconventional Extraction Of Carotenoidsmentioning
confidence: 99%
“…Nezammahalleh et al . (2016) applied a moderate static electric field (EF) to Chlorella vulgaris and found the algal cells showed a hormetic response to the pretreatment. The growth and total chlorophyll content showed an increase up to a maximum followed by a decline after the exposure to EF at different time.…”
Section: Introductionmentioning
confidence: 99%